1988
DOI: 10.1055/s-2006-962417
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids and Phenolics ofColchicum cilicicum1,2

Abstract: The distributions of the alkaloids colchicine, 2-demethylcolchicine, 3-demethylcolchicine, demecolcine, 2-demethyldemecolcine, and 3-demethyldemecolcine in the corms, stems, leaves, flowers, and seeds of COLCHICUM CILICICUM were analysed by HPLC. In addition, the alkaloids cornigerine, N-formyl- N-deacetylcolchicine, N-methyl-demecolcine, beta-lumicolchicine, gamma-lumicolchicine, beta-lumidemecolcine, gamma-lumidemecolcine, and N-ethoxycarbonyldemecolcine were identified, the last named being reported for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Previous studies have indicated that the composition of tropolone alkaloids differs in different parts of Colchicum species and varies during the different growth stages (Sütlüpınar et al, 1988;Husek et al, 1990;Alali et al, 2006). The aim of the present work was to determine the chemical constituents of the different parts (perigon, perigon tube, leaf, seed, and corm) of C. baytopiorum, an unexplored Turkish species, as a continuation of our studies on Colchicum species (Baytop & Özcöbek, 1970;Baytop et al, 1980;Sütlüpınar, 2002).…”
Section: Introductionmentioning
confidence: 79%
“…Previous studies have indicated that the composition of tropolone alkaloids differs in different parts of Colchicum species and varies during the different growth stages (Sütlüpınar et al, 1988;Husek et al, 1990;Alali et al, 2006). The aim of the present work was to determine the chemical constituents of the different parts (perigon, perigon tube, leaf, seed, and corm) of C. baytopiorum, an unexplored Turkish species, as a continuation of our studies on Colchicum species (Baytop & Özcöbek, 1970;Baytop et al, 1980;Sütlüpınar, 2002).…”
Section: Introductionmentioning
confidence: 79%
“…(Colchicaceae) was processed into three fractions (A-C) according to the schemes of Santavy, Preininger, Simanek, and Potesilova (1981) and Sutlupinar et al (1988). A high concentration of colchicinoids was noted in the TLC of fraction C by distinctive yellow spots after spraying with 5% phosphomolybdic acid in EtOH.…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
“…Dried plant material (537.7 g) was extracted with MeOH in a Soxhlet apparatus for 3 h. The solvent was evaporated under reduced pressure to yield a MeOHextract (148.1 g), which was fractionated based on the methods of Santavy et al (1981) and Sutlupinar et al (1988). Briefly, the MeOH-extract was dissolved in 5% acetic acid, extracted with light petroleum (Fraction A) (12.0 g), after which the aqueous acid residue was re-extracted three times with diethyl ether (Fraction B) (1.2 g).…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…This experiment was conducted to detect the effect of sucrose at different concentrations 0.0, 0.1, 0.2, 0.3 M on alkaloid production. Callus was subcultured to the MS media supplemented with different concentrations and data collected every other week for colchicine content using high performance liquid chromatography (HPLC) [18].…”
Section: Effect Of Nitrogen Sources and Concentration On Callus Growtmentioning
confidence: 99%
“…Several studies in the literature were reported to study (-)-colchicine content in pharmaceutical preparations, biological fluids and plant extracts [5,[16][17][18][19]. Production of colchicine alkaloid by plant tissue cultures was first investigated in suspension cultures of Colchicum autumnale [20,21].…”
Section: Introductionmentioning
confidence: 99%